MILK HANDLING: PROPOSALS RELATIVE TO THE AMENDMENT OF THE EXISTING LEGISLATION - ΣΚΟΥΝΤΖΟΣ, Κ.; ΠΑΠΑΔΙΑΣ, Α.; ΓΙΩΤΗΣ, Α. (Journal of the Hellenic Veterinary Medical Society, 1974)
In the present study the authors review the existing legislation on the handling of milk in Greece. The need for amending and or completing this legislation in axordance to international standards az they might be applicable in Greece is discussed, and the enforcement of certain measures is proposed.